Depictions of Murder in Maine: The Dominant Ideology Thesis. Issue 4 (3rd April 2019) - Riley, John
ABSTRACT: Recent research suggests that popular depictions of crime reflect and reinforce a dominant ideology in which criminals are viewed as rational actors who bear individual responsibility for crime. The research reported here employed a content analysis approach to examine depictions of 108 assailants found in media reports of murders that occurred in Maine from 2008 through 2012. While most of the depictions examined here describe crime as a matter of individual responsibility, this analysis found that many media depictions of Maine's murderers include content that is sympathetic to the offender and some accounts raise questions about the effectiveness of police services, mental health care and related social services.